2010
DOI: 10.1177/154193121005401930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Benefits and Potential Costs of Automation Delegation for Supervisory Control of Multiple UAVs

Abstract: Previous studies have begun exploring the possibility that “adaptable” automation, in which tasks are delegated to intelligent automation by the user, can preserve the benefits of automation while minimizing its costs. One approach to adaptable automation is the Playbook®interface, which has been used in previous research and has shown performance enhancements as compared to other automation approaches. However, additional investigations are warranted to evaluate both benefits and potential costs of adaptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Traditionally, human-automation interaction has been studied under a supervisory control framework, akin to a master-slave relationship (de Visser, Shaw, Mohamed-Ameen, & Parasuraman, 2010;Dzindolet, Pierce, Beck, Dawe, & Anderson, 2001;Muir, 1994;Muir & Moray, 1996;Satterfield, Ramirez, Shaw, & Parasuraman, 2012). However, research has shown that these supervisory control structures can potentially amplify cognitive demands on human operators as they struggle to integrate multiple information sources (Cosenzo, Parasuraman, & de Visser, 2010;Cummings & Mitchell, 2008;Shaw et al, 2010;Woods, Patterson, & Roth, 2002). Technological advances have allowed us to overcome the limitations associated with "automation-as-a-tool" control strategies and shift toward the use of autonomous, self-governing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, human-automation interaction has been studied under a supervisory control framework, akin to a master-slave relationship (de Visser, Shaw, Mohamed-Ameen, & Parasuraman, 2010;Dzindolet, Pierce, Beck, Dawe, & Anderson, 2001;Muir, 1994;Muir & Moray, 1996;Satterfield, Ramirez, Shaw, & Parasuraman, 2012). However, research has shown that these supervisory control structures can potentially amplify cognitive demands on human operators as they struggle to integrate multiple information sources (Cosenzo, Parasuraman, & de Visser, 2010;Cummings & Mitchell, 2008;Shaw et al, 2010;Woods, Patterson, & Roth, 2002). Technological advances have allowed us to overcome the limitations associated with "automation-as-a-tool" control strategies and shift toward the use of autonomous, self-governing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Playbook is an example of flexible delegation interactions with automation within the context of a task hierarchy-permitting human operators to select alternate levels and types of authority to hand off to automation and retain for themselves in different circumstances. Previously (Parasuraman, et al, 2005), and again in recent work (Fern & Shively, 2009;Shaw, et al, 2010), play-like, flexible delegation interactions with automation have been shown to have significant benefits in terms of overall performance and workload reduction across a variety of task contexts. In recent research, we have been exploring human performance with plays in multiple unmanned vehicle control scenarios under conditions where the plays do not "fit" well-that is, Non-Optimal Play Environment (NOPE) conditions.…”
Section: A Framework For Adaptive Aiding Through Delegation Interactimentioning
confidence: 95%
“…Several studies that have investigated adaptable automation based on task-delegation interfaces have found that this type of operator-initiated adaptive automation enhances performance [10][11][12]. Studies have also found that performance is highest when the delegation interface includes the highest level of abstraction (analogous to level of automation in this scheme), even when it is not appropriate for the current context.…”
Section: Operator Initiatedmentioning
confidence: 98%
“…While traditional approaches to operator-initiated adaptive automation typically define adaptability as shifting the level of automation (i.e., how much of the task is automated), several researchers have advocated for designing adaptive automation based on a hierarchical task delegation method [9][10][11][12]. In this adaptive automation scheme, the operator still has final decision authority over shifts in automation; however the functions are broken into predetermined tasks that the operator can choose to delegate to automation.…”
Section: Operator Initiatedmentioning
confidence: 99%
See 1 more Smart Citation